1967
DOI: 10.1136/jcp.20.2.152
|View full text |Cite
|
Sign up to set email alerts
|

Hypofibrinogenaemia in metastatic carcinoma of the prostate: suppression of systemic fibrinolysis by heparin

Abstract: SYNOPSIS In a patient with generalized prostatic carcinoma and hypofibrinogenaemia heparin infusion on four occasions abolished systemic fibrinolysis as determined by euglobulin clot lysis time, bovine fibrin plate assay, thromboelastography, and immunoelectrophoretic demonstration of fibrinogen split products.The pathogenesis of hypofibrinogenaemia in cases of prostatic carcinoma and the possibility of a direct heparin effect on fibrinolysis are discussed. Despite the lack of histological evidence for intrava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

1969
1969
1986
1986

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…By contrast, when control plasma C100 was exposed to plasmin (4 A'g plasmin/ml plasma at 370C for 3 h), fg-Dneo expression was readily generated as indicated by the competitive inhibition of ["I] fg-D binding. Plasmas from two patients with metastatic carcinoma and moderate levels of serum cleavage products by radial immunodiffusion ( X 100 = 5 mg/100 ml; X 101 = 8 mg/100 ml) were also assayed (8,32,33). Both produced semilogarithmic inhibition parallel to that produced by the in vitro cleaved plasma sample, indicating the appearance in vivo of fg-Dneo indistinguishable from that generated in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, when control plasma C100 was exposed to plasmin (4 A'g plasmin/ml plasma at 370C for 3 h), fg-Dneo expression was readily generated as indicated by the competitive inhibition of ["I] fg-D binding. Plasmas from two patients with metastatic carcinoma and moderate levels of serum cleavage products by radial immunodiffusion ( X 100 = 5 mg/100 ml; X 101 = 8 mg/100 ml) were also assayed (8,32,33). Both produced semilogarithmic inhibition parallel to that produced by the in vitro cleaved plasma sample, indicating the appearance in vivo of fg-Dneo indistinguishable from that generated in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmas were selected from patients with diseases associated with disseminated intravascular coagulation and the presence of circulating fibrin or fibrinogen cleavage fragments, e.g., metastatic carcinoma (8,32,33), abruptio placentae (6, 34), consumptive coagulopathy (disseminated intravascular coagulation) (8,35,36), meningococcal meningitis (37,38), and endotoxic shock (39,40). Serum cleavage fragments, primary evidence for in vivo fibrinolysis, were present in all (17-300 mg/100 ml).…”
Section: Resultsmentioning
confidence: 99%
“…It should be emphasized that heparin, in the doses given, would have no direct inhibitory effect on fibrinolysis; this is a biological effect in the intact organism, preventing the formation of fibrin appears to prevent fibrinolysis. In the experimental studies heparin has usually been given before the stimulus to coagulation but there is good evidence that heparin will also correct the changes in fibrinolysis in human patients already suffering from the effects of disseminated intravascular coagulation (Merskey, Johnson, Pert, and Wohl, 1964;Straub, Riedler, and Frick, 1967;Robboy, 1969). An example observed by the author is illustrated in Figure 3.…”
Section: Coagulation Versus Fibrinolysismentioning
confidence: 99%
“…Elucidation of the pathogenesis is important in view of the different mechanisms which require different therapeutic measures. Straub, Riedler, and Frick (1967) reported disseminated intravascular coagulation with hypofibrinogenaemia and secondary fibrinolysis in a case of generalized prostatic carcinoma which responded to heparin therapy. Tagnon, Schulman, Whitmore, and Leone (1953) found pathological fibrinolysis in a prostatic carcinoma and evidence of proteolytic activity in a bone metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…According to current concepts (McKay, 1965;Straub et al, 1967) the defibrination syndrome found in malignant disease is usually caused by disseminated intravascular coagulation. Certain cases remain, however, in which this is not a satisfactory explanation, and where investigation indicates primary pathological fibrinolysis as the pathogenetic mechanism.…”
Section: Introductionmentioning
confidence: 99%